(untitled) (Educação e Pesquisa, 2023)
This article presents the initial findings from the first phase of a study aimed at fostering research competencies in secondary school teachers by implementing a tailored model within the context of contemporary educational content. The primary objective of this research is to evaluate the efficacy of the devised model in cultivating research competencies among secondary school educators within the educational process. A comprehensive description of the teachers’ research competencies is provided, along with an exposition of their content components. We conducted an analysis of key, professional, and specialized pedagogical competencies, which informed the identification of essential research competencies for teachers as they pertain to the modernization of educational content. Subsequently, we developed a model for fostering research competencies in teachers within this context. Our analysis of preliminary experimental results suggests the need for modifications and refinements to the model, employing the hermeneutical phenomenology method during educational and professional interactions among participants in the educational process. The approaches and proposed model discussed in this article can be utilized in the development and enhancement of pedagogical research skills, as well as in continued professional development. Moreover, the findings of this study may be applicable in organizing a certification system for teaching staff, although that is not the primary focus of this research.